2020
DOI: 10.1142/s0219649220400158
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Association Rule Mining Technique for Predicting Chronic Kidney Disease

Abstract: Background and objective: Chronic kidney disease (CKD) is one of the deadly diseases that can affect a lot of vital organs in the human body such as heart, liver, and lungs. Many individuals might be at early stage of kidney disease and not have any signs, which might lead to a sudden death. Previous research showed that early prediction of CKD is very important in the medical field for physicians’ decision-making and patients’ health and life. To this end, constructing an efficient prediction system for CKD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Thus, for this example, the following association rules are developed: S5→(S2,S1); (S1,S5)→S2 and (S2,S5)→S1. It has been noticed that the apriori algorithm of association rule mining has already been successfully deployed for prediction/diagnosis of heart diseases (Said et al, 2015;Domadiya & Rao, 2018;Jamsheela, 2021), dengue (Jahangir et al, 2018), brain tumor (Sengupta et al, 2013), chronic kidney disease (Alaiad et al, 2020), infectious diseases (Brossette et al, 1998), pandemic diseases (Burvin & Dhanalakshmi, 2018;Aiswarya et al, 2020), COVID-19 (Çelik, 2020;Shawkat et al, 2021;Tandan et al, 2021), pediatric primary care (Downs & Wallace, 2000), treatment of patients in an emergency department (Sarıyer & Taşar, 2020) etc. In this paper, based on a huge dataset of COVID-19 patients and using the FP growth algorithm of association rule mining, an attempt is put forward to discover COVID-19 symptom patterns and rules which would support the initial identification of severe COVID-19 cases for early treatment and isolation.…”
Section: Association Rule Miningmentioning
confidence: 99%
“…Thus, for this example, the following association rules are developed: S5→(S2,S1); (S1,S5)→S2 and (S2,S5)→S1. It has been noticed that the apriori algorithm of association rule mining has already been successfully deployed for prediction/diagnosis of heart diseases (Said et al, 2015;Domadiya & Rao, 2018;Jamsheela, 2021), dengue (Jahangir et al, 2018), brain tumor (Sengupta et al, 2013), chronic kidney disease (Alaiad et al, 2020), infectious diseases (Brossette et al, 1998), pandemic diseases (Burvin & Dhanalakshmi, 2018;Aiswarya et al, 2020), COVID-19 (Çelik, 2020;Shawkat et al, 2021;Tandan et al, 2021), pediatric primary care (Downs & Wallace, 2000), treatment of patients in an emergency department (Sarıyer & Taşar, 2020) etc. In this paper, based on a huge dataset of COVID-19 patients and using the FP growth algorithm of association rule mining, an attempt is put forward to discover COVID-19 symptom patterns and rules which would support the initial identification of severe COVID-19 cases for early treatment and isolation.…”
Section: Association Rule Miningmentioning
confidence: 99%
“…A current literature review in [13], [14], related to the dimensionality reduction problem in medical dataset classification showed that the issue of irrelevant feature on the accuracy of classification model is still an ongoing and open research issue. Developing classification model with higher accuracy on medical ISSN: 2302-9285  An improved feature selection approach for chronic heart disease … (S. J. Sushma)…”
Section: Litreature Rebviewmentioning
confidence: 99%
“…Creatinine levels in the blood increase with reduced kidney activities. Researches (Levey et al 1999(Levey et al , 2009Alaiad et al 2020;Elhoseny et al 2019;Qin et al 2019) show that the most commonly used prediction factors for CKD diagnosis are serum creatinine, age, serum urea, and specific gravity. From different research studies performed in different random samples, it has been observed that close associations are present between enhanced albuminuria (presence of albumin in the urine) and kidney failure (Chronic Kidney Disease Prognosis Consortium, 2010).…”
Section: Dataset and Attributesmentioning
confidence: 99%